The effect of emotional intelligence on employee performance with self-efficacy as a moderating variable (Lighthouse Publishing, 2022)
Employees are resources that play an active role in setting plans, systems, processes, and goals to be achieved effectively and efficiently for the progress of a company so; that employees need to be managed as well as possible to achieve the goals that have been set. Managing and coaching employees as superior human resources must be supported by high employee emotional intelligence. In addition to emotional intelligence, a person's belief in self-efficacy will encourage him to try to get what he wants. So, employees with high emotional intelligence and self-efficacy can provide optimal performance for the company. This study aims to determine the effect of emotional intelligence on employee performance with self-efficacy as a moderating variable. The object of this research is the employees of PT Lautan Berlian Utama Motor Lampung. The form of this research is descriptive research with a quantitative approach. This research uses Moderated Regression Analysis (MRA). The results of the study show that there is an effect of emotional intelligence on employee performance, and self-efficacy can strengthen the influence of emotional intelligence on employee performance.